Pengembangan E-Magazine Berbasis Media Interaktif Terhadap Kreativitas Siswa pada Materi Keanekaragaman Hayati di SMAS Al-Ma’shum Kisaran Barat - Audia Fadilla; Rahmadina (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop an interactive media-based E-Magazine that is feasible, practical, and effective in enhancing students’ creativity on biodiversity material at SMAS Al-Ma’shum Kisaran Barat. This study employed a Research and Development (R&D) method using the 4D development model, consisting of the define, design, develop, and disseminate stages. The research subjects were 32 students of class X-3 at SMAS Al-Ma’shum Kisaran Barat in the 2025/2026 academic year. Data were collected through material and media expert validation sheets, teacher and student response questionnaires, and students’ creativity tests. The results showed that the developed E-Magazine achieved a feasibility score of 92.5%, categorized as highly feasible. The practicality level reached 94.7% based on students’ responses and 95% based on the teacher’s response, both categorized as highly practical. The effectiveness of the E-Magazine was indicated by an increase in students’ average creativity score from 32.19 in the pretest to 83.28 in the posttest, with an N-Gain score of 0.75, which was categorized as high. Therefore, the interactive media-based E-Magazine developed in this study was highly feasible, highly practical, and effective for biology learning and could enhance students’ creativity in biodiversity learning. Keywords: Biodiversity, E-Magazine, Interactive Media, Media Development, Student Creativity